Effects of impulse-cyclone drying and silane modification on the properties of wood fiber/HDPE composite material. (1st March 2019) - Gao, Xun; Lin, Lin; Pang, Jiuyin; Chen, Feng; Li, Qingde
Highlights: The ICD/silane co-modification is a very efficient and environmentally-friendly modification method, it could significantly reduce the amount of hydroxyl groups and polarity of the wood fibers and improve the compatibility and dispersion of wood fibers in plastics. After ICD pretreatment, the surface polarity of the fibers decreased, which allowed the addition of a small amount of silane could be the maximum mechanical properties of the composites and reduced the modification cost. The co-modification could significantly enhance the hydrophobicity, crystallinity, and thermostability of the fibers and composites. The ICD/silane co-modification provided even better physical and mechanical properties of the WPCs than that only modified by silane or impulse-cyclone drying. Abstract: Poplar fibers were pretreated under impulse-cyclone drying (ICD) and further modified by different types of silane with special chemical structures. The effects of ICD-assisted silane modification on the properties of wood plastic composites (WPCs) were investigated. The main findings indicated that the number of hydroxyl groups and the polarity of the fibers decreased after the ICD/silane co-modification, whereas the hydrophobicity and crystallinity of fibers, the compatibility and adhesion strength between fibers and plastics, and the mechanical properties, thermostability, and dynamic mechanical properties of WPCs were significantly improved. In this study, when the wood fibers were only modified by silane and the silane content was 5%, the WPCs had better properties, and the WPCs modified with vinyl tri-methoxysilane (A-171) had the best properties. Furthermore, the addition of a small amount of silane to the wood fibers modified by ICD provided even better physical and mechanical properties compared to those of the WPCs that were only modified by silane; when 3% silane was added, there were increases of 10.67%, 10.22% and 9.4%, in the tensile, flexural and impact strengths, respectively, and an increase of 6.84% in the contact angle of the composites. The water absorption rate of the composite significantly decreased as well.